Perlindungan Hukum Bagi Konsumen terhadap Wanprestasi dalam Perjanjian Jual Beli Purchase Order (Po) Melalui Media Online - Made Irnanda Diandifa Lestari; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Interpretasi Hukum, 2022)
Today, information and communication technology has provided many changes to human life. With the development of technological sophistication, this buying and selling process can be carried out without meeting the seller and the buyer. Trading activities through the use of the internet are called electronic commerce or what is known as the abbreviation e-commerce. This study aims to analyze and describe the legal protection for consumers against default in buying and selling agreements through online media. In this study using the normative method, by tracing various aspects. Legal materials are sourced from legislation, collected through documentation and literature studies. The results of the study indicate that Purchase orders (PO) can be said to be evidence of buying and selling transactions through electronic media because when viewed from the form and content of the purchase order is a valid sale and purchase agreement. In addition, business actors can be prosecuted through an authorized institution in resolving disputes by harmed consumers, or it can also be resolved through peaceful means.